HOW IS ESD (EDUCATION FOR SUSTAINABLE DEVELOPMENT) IMPLEMENTED AFTER COVID-19 IN INDONESIA TO REALIZE SDG's? - Mardian, Vivi (Physics and Science Education Journal (PSEJ), 2023)
Sustainable development is very important for the progress of the country. Teachers have a role in educating the younger generation to master 21st-century skills. 21st century skills are one of the keys to realizing the 17 SDGs for Indonesia's progress. This research aims to determine the implementation of ESD (Education for Sustainable Development)-based learning after COVID-19 in Indonesia. This research uses a literature review approach with descriptive analysis techniques. The articles were collected from 10 articles published between 2021 and 2023. The keyword used to collect articles is ESD. The SLR research steps consist of three stages, namely planning, implementation, and reporting. The research results show that ESD is applied to lower, upper secondary, and vocational school students and teachers. In addition, ESD is researched using mixed methods: qualitative, quantitative, quasi-experimental, and R&D. ESD learning is able to improve students' 21st century skills, knowledge, and environmental awareness. Future research needs to examine the implementation of ESD at the tertiary level and teachers' readiness to teach science-based ESD.